Particle swarm optimization technique for optimizing load flow analysis / Muhammad Syafiq Mohd Zaman - Mohd Zaman, Muhammad Syafiq (2009)
The state of power system and methods of calculating this state are extremely important in evaluating the operation of the power system, the control of this system and the determination of future expansion for the power system. The state of power system is determined through load flow analysis that calculates the power flowing in the lines of the power system especially in determining the total losses in the power system. Particle swarm optimization (PSO) is a stochastic global optimization algorithm inspired by social behavior of bird flocking in search of food, which is simple but powerful, and widely used as a problem solving technique to a variety of complex problems in science and engineering. The PSO technique was proposed to solve on Institute of Electrical & Electronic Engineers (IEEE) 30-bus system. The proposed technique was able to minimize the losses in the power system with results of losses minimization.